Circulating long non‐coding RNA Coromarker expression correlated with inflammation, coronary artery stenosis, and plaque vulnerability in patients with coronary artery disease. Issue 11 (26th September 2022) - Liu, Gang; Hu, Xun; Li, Yi; Long, Ming
Abstract: Background: The aim of the study was to assess the correlation between circulating long non‐coding RNA (lncRNA) OTTHUMT00000387022 (named Coromarker) expression and disease severity, inflammatory cytokine levels, and plaque vulnerability in patients with coronary artery disease (CAD). Methods: A total of 134 participants who received coronary angiography were enrolled and classified them as CAD patients ( N  = 89) and controls ( N  = 45). Blood samples were obtained from all subjects. Quantitative polymerase chain reaction was used to evaluate Coromarker expression. The enzyme‐linked immunosorbent test was used to measure inflammatory cytokines including high sensitivity C reactive protein (hsCRP), interleukin (IL)‐1 β (IL‐1 β ), IL‐6, NOD‐like receptor protein 3 (NLRP3), and markers of coronary plaque stability including matrix metallopeptidase 9 (MMP‐9) and soluble CD40 ligand (sCD40L). The severity of coronary stenosis was determined from the Gensini Score. Results: LncRNA Coromarker expression was elevated to a greater extent in CAD patients than in control subjects before and after adjustments for age/gender (both p  < 0.001); it was an independent predictor of CAD risk (area under curve: 0.824, 95% CI: 0.732–0.915). Additionally, Coromarker expression was significantly associated with Gensini Score ( r  = 0.574, p  < 0.001), hsCRP ( r  = 0.221, p  = 0.015), IL‐1 β ( r  = 0.351, p  < 0.001), IL‐6 ( r  = 0.286, p  < 0.01), and NLRP3 levels ( r  = 0.312, p  < 0.001). Coromarker expression was found to be linked with MMP‐9 ( r  = 0.260, p  < 0.01) and sCD40L ( r  = 0.441, p  < 0.001). Conclusion: Circulating lncRNA Coromarker expression correlates with increased disease severity and inflammation as well as plaque vulnerability in patients with CAD. Abstract : Circulating lncRNA Coromarker expression correlates with higher disease severity, elevated inflammation, and plaque vulnerability in CAD patients. Association between lncRNA Coromarker and Gensini Score in CAD patients. LncRNA Coromarker positively correlated with inflammatory cytokines in CAD patients, including hsCRP, IL‐1 β, IL‐6, and NLRP3. LncRNA Coromarker was increased in ACS patients compared with CCS patients and control subjects. LncRNA Coromarker expression was positively associated with troponin T, MMP‐9, and sCD40L.